Анализ спектральных характеристик звуковых сигналов ластоногих - Свиженко, В.А. (Вестник зоологии, 1983)
Spectral characteristics of sound signals in representatives of three Pinniped families (Phocidae: Phoca vitulina, Erignathus barbatus; Otariidae: Eumetopias jubatus; Odobenidae: Odobenus rosmarus) are analyzed to show their differences. Random time samples of the signals were used as initial material for the analysis. Sound frequency ranges and values of their detection probability are given.